2022
DOI: 10.1186/s12880-022-00916-0
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning approach for automated diagnosis of pulmonary embolism on computed tomographic pulmonary angiography

Abstract: Background Computed tomographic pulmonary angiography (CTPA) is the diagnostic standard for confirming pulmonary embolism (PE). Since PE is a life-threatening condition, early diagnosis and treatment are critical to avoid PE-associated morbidity and mortality. However, PE remains subject to misdiagnosis. Methods We retrospectively identified 251 CTPAs performed at a tertiary care hospital between January 2018 to January 2021. The scans were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…They tested the model performance on a single external dataset consisting of CTAs from 251 patients of whom 55 presented PE. Sensitivity and specificity were 80% and 74% respectively with an accuracy of 0.76 [ 25 ]. Huang et al developed and evaluated an end-to-end DL model capable of detecting PE using the entire volumetric CTA imaging examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They tested the model performance on a single external dataset consisting of CTAs from 251 patients of whom 55 presented PE. Sensitivity and specificity were 80% and 74% respectively with an accuracy of 0.76 [ 25 ]. Huang et al developed and evaluated an end-to-end DL model capable of detecting PE using the entire volumetric CTA imaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…The radiologist’s sensitivity for detecting PE has been measured in the range of 67 to 87% with a specificity of 89 to 99% [ 17 , 18 , 19 ]. Studies have reported promising results in applying deep learning (DL) models to automate PE diagnosis on CTA [ 20 , 21 , 22 , 23 , 24 , 25 ]. In a systematic review with the meta-analysis of DL-based AI algorithms developed to detect PE on CTA, published in 2021, five studies provided enough data to calculate the test accuracies [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…38 Given that pulmonary embolism can be clinically misdiagnosed or missed in up to one-fourth of patients, 39 several groups have worked on ML-based automatic detection models for this clinical event. 38,40,41 A deep learning model (PENet) for automatic detection of pulmonary embolism from volumetric computed tomography (CT) pulmonary angiograms was developed that achieved an AUROC of 0.85 [95% CI 0.81-0.87] on an external dataset. 42 Such tools can be envisioned to serve as secondary reading tools and also prioritize scans in radiologist review queues to prevent delays in diagnosis.…”
Section: Machine Learning Applications For Image Recognition In Venou...mentioning
confidence: 99%
“…In another article [18], a 2D segmentation model of the U-Net-based architecture classification algorithm was developed and tested targeting the diagnosis of pulmonary embolism. The researchers used a clinical dataset containing 251 computerized tomography pulmonary angiograms (CTPAs).…”
Section: Pulmonary Systemmentioning
confidence: 99%
“…The researchers used a clinical dataset containing 251 computerized tomography pulmonary angiograms (CTPAs). Setting a calibration that aimed at minimizing false negative rates, they calculated that blood clots in the main pulmonary and segmental arteries could be detected with 93% sensitivity and 89% specificity (Pranav Ajmeral et al, 2022) [18] (Table 1). Another study that utilized CAD for the detection of pulmonary embolism by means of multiaxial segmentation [19] indicated an obvious superiority of the 2.5D training method over the 2D network architectures but no clear difference between the 2.5D and 3D method.…”
Section: Pulmonary Systemmentioning
confidence: 99%